Implementasi Nilai-Nilai Pendidikan Agama Islam dalam Membentuk Karakter Religius Peserta Didik Era Digital di Madrasah Tsanawiyah - Indriani, Dea; Aliyyah Putri Azzahra; Novita Zahara (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
This study aims to examine the implementation of Islamic Religious Education (IRE) values in shaping students' religious character in the digital era at Islamic Junior High Schools (Madrasah Tsanawiyah). The study employed a Systematic Literature Review (SLR) method by analyzing scientific articles obtained from Google Scholar, Garuda, and SINTA databases published between 2021 and 2026. The research process involved identification, selection, evaluation, and synthesis of literature relevant to the research focus. The findings indicate that the implementation of Islamic Religious Education values in shaping students' religious character is centered on three main pillars: aqidah (faith), sharia (Islamic practices), and akhlaq (morality). These values are implemented through Islamic Religious Education learning, religious habituation programs, religious school culture, and teacher role modeling. Strategies used in developing students' religious character include active learning, religious habituation, exemplary conduct, and collaboration between schools and parents. Supporting factors include a religious school environment, structured religious programs, parental support, and the use of technology as a learning medium. Meanwhile, inhibiting factors include the negative influence of social media, uncontrolled access to information, and inadequate supervision of technology use. This study concludes that the consistent and sustainable implementation of Islamic Religious Education values can effectively shape students' religious character, enabling them to use technology wisely while maintaining Islamic values.